The linkage between relative population growth and purchasing power parity: cross country evidence - Hassan, K.; Salim, Ruhul (Emerald Group Publishing Ltd., 2011)
Purpose – The aim of this paper is to examine the relationship between relative population growth and purchasing power parity (PPP) exchange rate for a panel of 80 countries. Design/methodology/approach – Panel unit root and panel cointegration tests have been used to investigate the above relationship over the period of 1951-2000. Findings – The empirical results show that there is stable relationship between PPP exchange rate and relative population growth in these selected countries in the long run. The results also show that this long-run relationship remains valid when the sample is divided on the basis of their stage of development. Practical implications – These empirical findings suggest that population growth has an important role in exchange rate determination through PPP. Originality/value – Thus, relative population growth could invalidate the PPP hypothesis in the long run. PPP is the main edifice of most of the monetary exchange rate models. Hence, the role of relative population growth should be taken into account in dealing with issues in international macroeconomics and renewed attention should be given in the theory of exchange rate determination in terms of relative population growth instead of relative price level.